LIPOMA INTERMUSCULAR EM CÃO: RELATO DE CASO - Morais, Laura Eliza; Schmidt, Marília; Morais, Ariane Liara; Ben, Ângela Guedes; Klaus, Vinicios Boff; Serafini, Gabriele Maria Callegaro (Salão do Conhecimento, 2018)
Caso Cirúrgico acompanhado na disciplina de Patologia e Clínica Cirúrgica Unijuí